THE USE OF JIGSAW TO IMPROVE THE STUDENTS READING COMPETENCE OF THE TENTH GRADE STUDENTS OF SMK DWIJENDRA DENPASAR IN THE ACADEMIC YEAR 2018/2019 - Mardiana Elu; I Gusti Ayu Indah Triana Juliari (Widyasrama, 2020)
This research was to improve Grade X students’ reading competence by the using Jigsaw in SMK Dwijendra Denpasar. It was an action research study which consisted of two cycles. The researcher worked collaboratively with the English teacher, and the students. The subjects of the research were students of X grade AK1 of SMK Dwijendra Denpasar in the academic year of 2018/2019. The quantitative data were collected through the students’ reading competence of the pretest and post-test 1 and 2. The procedure of the research consisted of planning, observing, acting, and reflecting. The results of this research showed that the use Jigsaw was successful improve the students’ reading competence. Based on the quantitative data, the use of Jigsaw helped the students to understand narrative text and to be more familiar with English. It also helped them to enrich their vocabulary and build their knowledge. Furthermore, the use of Jigsaw could attract their attention during the class. Based on the quantitative data, the students’ mean scores for the reading competence improved from 60% in the pretest to in post-test 1 70% and posttest II 80%.